Dekonstruksi Haji Dan Umrah Dalam Dakwah - Afif Via Syahdaniya; Samsul Rifa’i (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2021)
The da'wah model that is increasingly dynamic is caused by the development of the times and technological advances. The development of the modern era which is actually experiencing a setback has become a phenomenon that is happening today. Changes in the process of Hajj and Umrah at this time need to be adjusted to the principles of Islamic da'wah fiqh in the teachings of Islam. The implementation of the Hajj and Umrah pilgrimages, which should be easier by looking at the flashbacks of the Hajj process in ancient times, is in fact currently experiencing a setback with conditions that are not good or even bad. Hajj and Umrah, which are supposed to be the most sacred journeys of worship to the Baitullah, are in fact currently happening many phenomena wrapped in a desire to fulfill emotional needs. This research was carried out using the library research method in several journals and books related to this discussion. This is discussed differently such as how the process of Hajj and Umrah in ancient times underwent changes in today's modern times. Hajj and Umrah are not ordinary journeys, but in them there is a journey of worship to fulfill the call of Allah SWT along with the spiritual and inner heart of a Muslim. So it is not appropriate if the pilgrimage and umrah are mixed with worldly affairs.